(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
Group interactive art therapy is a way to solve various socio-pedagogical problems. Each group interactive art therapy technology works with the concept of the child’s "I", offering new solutions to problems that the child independently identifies through group activity, using the resources of creativity, awakening of inner abilities, talents and self-understanding. Depending on what task this group interactive art therapy solves, groups are divided according to different methodologies: according to the socio-pedagogical goal, according to the age characteristics of children, according to the use of various communication models, etc. Since the goals of individual art therapy technologies and group interactive art technologies are different, we can say that they solve different tasks and develop children’s independent abilities for psychoregulation, correction of emotional deformations, discharge and loading of the spiritual world.